A palladium-catalyzed one-pot procedure for the regioselective dimerization and cyanation of indoles - Kianmehr, Ebrahim; Ghanbari, Mohammad; Rominger, Frank (Tetrahedron letters, 2012)
A one-pot method for the regioselective dimerization and cyanation of indoles has been developed. The reaction uses safe and nontoxic K4[Fe(CN)6]·3H2O as the cyanating agent which introduces selectively a cyano group into the 3-position of biindoles with high efficiency.